Witnesses to the Struggle : Imaging the 1930s California Labor Movement - Loftis, Anne, 1922- (Book collections on Project MUSE., 1998)
In Witnesses to the Struggle, Anne Loftis focuses on the work and activities of John Steinbeck, Carey McWilliams, Paul Taylor, and Dorothea Lange, who brought the story of California's labor struggles to the rest of the country. The realism and documentary expression of their art grew out of their personal involvement in the problems of society, and Loftis explores the lasting influence of their work as well as its remarkably immediate impact. One of Steinbeck's unintended legacies was his treatment of California farm workers as victims - the simple pawns of larger forces. In her study, Loftis reveals that the workers were not victims, but rather the strong and resourceful creators of their own histories.